2022
DOI: 10.3389/fvets.2022.1028792
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium autoethanogenum protein inclusion in the diet for broiler: Enhancement of growth performance, lipid metabolism, and gut microbiota

Abstract: This study aimed to investigate the effects of dietary supplementation of the new single-cell protein Clostridium autoethanogenum protein (CAP) on growth performance, plasma biochemical indexes, liver histology, lipid metabolism, and gut microbiota in Cobb broilers. According to the randomized block experimental design, 960 Cobb broilers (1d old) were divided into six treatments with eight replicates of 20 birds each. Six isonitrogenous and isoenergetic diets were formulated with different contents of CAP (0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 80 publications
6
3
0
Order By: Relevance
“…Hyperuricemia and gout can be caused by overproduction or reduced excretion of UA (39). Previous study has shown that the inclusion of CAP in diets can increase TP and ALB levels, and UA levels also tend to increase with increasing CAP content (34), which is consistent with the results of the present study. TC and TG are the main lipids in the blood and important indicators of lipid absorption, metabolism, and transport (40,41).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Hyperuricemia and gout can be caused by overproduction or reduced excretion of UA (39). Previous study has shown that the inclusion of CAP in diets can increase TP and ALB levels, and UA levels also tend to increase with increasing CAP content (34), which is consistent with the results of the present study. TC and TG are the main lipids in the blood and important indicators of lipid absorption, metabolism, and transport (40,41).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, CAP had a significant effect on the lipid metabolism of broilers, as evidenced by the decrease in TG levels. This finding is consistent with the results reported by Wu et al (34) but differs from those observed in aquatic animals (11,27), which may be attributed to species differences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations